Conduction properties of Ti‐doped NaTaO3 at intermediate temperature. Issue 12 (19th July 2021) - Chen, Ximu; Hatada, Naoyuki; Toyoura, Kazuaki; Uda, Tetsuya
Abstract: In this work, the ionic conductivity and charge carriers of acceptor‐doped sodium tantalate (NaTaO3 ) with perovskite structure were investigated at intermediate temperatures. The Ta‐site of NaTaO3 was doped with up to 20% titanium (Ti) with the conventional solid‐state reaction method. After calcination at 900°C, samples nominally doped with 5, 10% Ti show X‐ray diffraction (XRD) pattern of orthorhombic NaTaO3 only, while peaks of Na2 Ti3 O7 can be observed in those doped with 15, 20% Ti. The conductivity of undoped, 5% Ti and 10% Ti‐doped NaTaO3 at 300°C–700°C was measured with electrochemical impedance spectroscopy (EIS) under dry and wet O2 atmospheres. Ti‐doped NaTaO3 samples have higher conductivity in the wet atmosphere than in the dry atmosphere, reaching 3 × 10 −4 S/cm at 700°C (10% Ti‐doped NaTaO3 ), which confirms the hydration and proton conduction in Ti‐doped NaTaO3 . Through the investigation on the dependence of conductivity on oxygen partial pressure, hole conduction in an oxidizing atmosphere, and electron conduction in reducing atmosphere can be verified. Na + conduction was proven to be negligible with direct current polarization.